PERANAN GURU DALAM UPAYA MENINGKATKAN PEMBELAJARAN PENDIDIKAN ANAK USIA DINI BUDDHIS DI KECAMATAN GETASAN - Santoso, Edi; Suranto, Suranto; Dewi, Sukhitta (Jurnal Pencerahan, 2021)
This research is motivated by the insufficiency of PAUD Buddhist teachers in Getasan Subdistrict in playing themselves roles as teachers when teaching in class. This study aims to determine the role of teachers in efforts to improve the learning process of Buddhist PAUD in Getasan District. This research is a study with a qualitative approach. The data was collected through observation, direct and semi-structured interviews, and documentation. The analysis used models from Miles and Huberman. The results of the teacher's role in efforts to improve Buddhist PAUD learning in Getasan District are as follows: (1) Buddhist PAUD teachers in Getasan Subdistrict have been able to improve learning well, be able to master the four abilities of their own, able to portray themselves as teachers well, and able to control the class when teaching and learning activities take place; (2) Efforts made by Buddhist PAUD teachers in Getasan District have been able to control the classroom atmosphere and can overcome obstacles quite well. namely, the teacher is always able to attract the attention of students when students have experienced boredom through the provision of icebreaking and the use of interesting learning media.